White Matter Correlates of Musical Anhedonia: Implications for Evolution of Music - Loui, Psyche; Patterson, Sean; Sachs, Matthew E.; Leung, Yvonne; Zeng, Tima; Przysinda, Emily (Frontiers in Psychology, 2017)
Recent theoretical advances in the evolution of music posit that affective communication is an evolutionary function of music through which the mind and brain are transformed. A rigorous test of this view should entail examining the neuroanatomical mechanisms for affective communication of music, specifically by comparing individual differences in the general population with a special population who lacks specific affective responses to music. Here we compare white matter connectivity in BW, a case with severe musical anhedonia, with a large sample of control subjects who exhibit normal variability in reward sensitivity to music. We show for the first time that structural connectivity within the reward system can predict individual differences in musical reward in a large population, but specific patterns in connectivity between auditory and reward systems are special in an extreme case of specific musical anhedonia. Results support and extend the Mixed Origins of Music theory by identifying multiple neural pathways through which music might operate as an affective signaling system.